Monosodium Urate in the Presence of RANKL Promotes Osteoclast Formation through Activation of c-Jun N-Terminal Kinase - Jung-Yoon Choe; Ki-Yeun Park; Seong-Kyu Kim (Hindawi Limited, 2015)
The aim of this study was to clarify the role of monosodium urate (MSU) crystals in receptor activator of nuclear factor kB ligand- (RANKL-) RANK-induced osteoclast formation. RAW 264.7 murine macrophage cells were incubated with MSU crystals or RANKL and differentiated into osteoclast-like cells as confirmed by staining for tartrate-resistant acid phosphatase (TRAP) and actin ring, pit formation assay, and TRAP activity assay. MSU crystals in the presence of RANKL augmented osteoclast differentiation, with enhanced mRNA expression of NFATc1, cathepsin K, carbonic anhydrase II, and matrix metalloproteinase-9 (MMP-9), in comparison to RAW 264.7 macrophages incubated in the presence of RANKL alone. Treatment with both MSU crystals and RANKL induced osteoclast differentiation by activating downstream molecules in the RANKL-RANK pathway including tumor necrosis factor receptor-associated factor 6 (TRAF-6), JNK, c-Jun, and NFATc1. IL-1b produced in response to treatment with both MSU and RANKL is involved in osteoclast differentiation in part through the induction of TRAF-6 downstream of the IL-1b pathway. This study revealed that MSU crystals contribute to enhanced osteoclast formation through activation of RANKL-mediated pathways and recruitment of IL-1b. These findings suggest that MSU crystals might be a pathologic causative agent of bone destruction in gout.